Desentralisasi dan Komodifikasi Barang Publik: Kajian Marxis atas Komersialisasi Taman Kiara Kota Bandung - Maghfiroh, Hani; Dede Sri Kartini (Universitas Serang Raya, 2024)
This study aims to analyze how decentralization and public-private partnerships in the management of Kiara Artha Park in Bandung have led to new forms of commodification of public space, using a Marxist perspective. This research employs a qualitative approach through library research methods. Data were obtained from academic documents, government policies, media articles, and critical theoretical literature. The analysis was conducted thematically using deductive-inductive reasoning, grounded in Marxist theories of capital, space, and power. The findings reveal that Kiara Artha Park has transformed from a democratic public space into a semi- private area governed by capitalist rationality. Commodification manifests through entrance fees, commercialized facilities, and the dominance of local capital in its management structure. The project illustrates how local governments function more as facilitators of capital than protectors of public interest, while local capitalists become dominant actors in the reproduction of spatial value. The study concludes that decentralization without ideological control strengthens spatial inequality and erodes citizens rights to the city. The study recommends anti-commodification regulations and enhanced citizen participation in urban spatial governance.